Influence of hydrated protons on temperature and humidity responsiveness of silk fibroin hydrogel ionotronics. (March 2021) - Yang, Shuo; Liu, Qiang; Ren, Jing; Ling, Shengjie
Highlights: The role of hydrated protons in the conduction of hydrogel ionotronics is studied. Hydrogel ionotronics show distinct responses to temperature and humidity. Hydrogel ionotronics display decoupled responses to temperature and humidity. Summary: Silk fibroin hydrogel ionotronics (SFHIs) have received increasing attention due to their good mechanical and electrical adjustability, as well as their environmental responsiveness and friendliness. However, fundamental issues related to the conductivity mechanisms and their influences on the temperature and humidity responses are still unclear. In this study, the conductive mechanisms of SFHIs were investigated by combining the experimental characterization with the theoretical analysis. The results suggested the vital role of hydrated protons in the conduction mechanism of SFHIs. The hydrated protons significantly affected the temperature and humidity responses of SFHIs with behaviors obeying distinct theoretical models. Precisely, the temperature response followed the rate of proton rearrangement reaction, while humidity response obeyed the percolation theory. Hence, a combined model was developed to decouple the experimental temperature and humidity responses of SFHIs during synchronic variation. In sum, a rational approach for decoupling the temperature and humidity responses of SFHIs was successfully developed, suitable for future design of smart SFHIs. Graphical abstract: Image, graphical abstract